2022
DOI: 10.1111/joim.13496
|View full text |Cite
|
Sign up to set email alerts
|

The potential of DNA methylation as a biomarker for obesity and smoking

Abstract: Heikkinen A, Bollepalli S, Ollikainen M. The potential of DNA methylation as a biomarker for obesity and smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 183 publications
(239 reference statements)
0
11
0
3
Order By: Relevance
“…Nearly all patients with cancer were male, tended to have a lower BMI, and had a history of drinking and smoking. It has been reported that in addition to cancer, DNA methylation could be affected by lifestyle habits such as smoking and obesity [ 43 ]. However, multivariate logistic regression analysis showed that, the DCC methylation cut-off value set in this study was not significantly affected by patient background factors, including smoking and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all patients with cancer were male, tended to have a lower BMI, and had a history of drinking and smoking. It has been reported that in addition to cancer, DNA methylation could be affected by lifestyle habits such as smoking and obesity [ 43 ]. However, multivariate logistic regression analysis showed that, the DCC methylation cut-off value set in this study was not significantly affected by patient background factors, including smoking and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The modifiable nature of epigenetic marks makes them key targets for future therapies. DNA methylation is a well-studied and stable form of epigenetics, and it has been shown that the alterations of DNA methylation are related to many diseases [ 14 , 15 , 16 , 17 ]. This has drawn increasing attention to the importance of methylation in the pathophysiology of AS.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in DNA methylation levels in peripheral blood leukocytes reflect genetic imprinting, environmental exposures, and the lineage differentiation that gives rise to immune cell subtypes [ 5 ]. Recent studies using epigenetic markers in blood have identified differentially methylated regions in smokers [ 6 , 7 ]; DNA methylation levels in these regions remained strongly associated with lung cancer mortality after adjusting for smoking history [ 6 ]. Epigenetic aging measures or “clocks” have also been developed to reflect biological age in tissue and blood [ 8 ].…”
Section: Introductionmentioning
confidence: 99%